2010
DOI: 10.1029/2009jd011981
|View full text |Cite
|
Sign up to set email alerts
|

Isentropic modeling of a cirrus cloud event observed in the midlatitude upper troposphere and lower stratosphere

Abstract: [1] This publication provides a detailed study of one cirrus cloud observed by lidar at the Observatory of Haute-Provence ($44°N) in January 2006 in the vicinity of the tropopause (12)(13)(14). The higher part of the air mass observed comes from the wet subtropics while the lower part comes from the midlatitudes. Both are advected by the Azores anticyclone, encounter cold temperatures ($205 K) above the North Atlantic Ocean, and flow eastward along the anticyclonic flank of the polar jet stream. A simulation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 83 publications
4
10
0
Order By: Relevance
“…In a study that related climate sensitivity to atmospheric global climate model (GCM) parameters, Sanderson et al (2008) identified the ice crystal fall speed as the second most influential parameter to climate sensitivity, and a decrease in fall speed was related to an increase in cirrus cloud coverage, humidity and long-wave cloud forcing. Similar conclusions have been obtained using Lagrangian numerical simulations (Montoux et al, 2010). It has been also demonstrated (Jakob, 2002) that, in the weather 458 D. Dionisi et al: Cirrus crystal fall velocity estimates using Match method: case study investigation forecast model of the European Centre for Medium Range Weather Forecast (ECMWF), the global mean integral radiation flux divergence decreases from 110 W m −2 to 90 W m −2 for assumed fixed values of the crystal fall speed from 0.1 to 2 m s −1 .…”
Section: Introductionsupporting
confidence: 73%
“…In a study that related climate sensitivity to atmospheric global climate model (GCM) parameters, Sanderson et al (2008) identified the ice crystal fall speed as the second most influential parameter to climate sensitivity, and a decrease in fall speed was related to an increase in cirrus cloud coverage, humidity and long-wave cloud forcing. Similar conclusions have been obtained using Lagrangian numerical simulations (Montoux et al, 2010). It has been also demonstrated (Jakob, 2002) that, in the weather 458 D. Dionisi et al: Cirrus crystal fall velocity estimates using Match method: case study investigation forecast model of the European Centre for Medium Range Weather Forecast (ECMWF), the global mean integral radiation flux divergence decreases from 110 W m −2 to 90 W m −2 for assumed fixed values of the crystal fall speed from 0.1 to 2 m s −1 .…”
Section: Introductionsupporting
confidence: 73%
“…Thin cirrus clouds (∼ 1 km) in the upper troposphere (similar to class 3) have already been observed over OHP, investigated and found to be associated with air masses coming from subtropical regions. Numerical simulations using an isentropic transport model were able to reproduce such type of clouds (Montoux et al, 2010), confirming they originate in the isentropic transport of moist air from subtropical regions to midlatitudes and can be classified as synoptic cirrus. They are formed into filamentary wet tongues, and appear a relatively short time on lidar observations.…”
Section: Summary and Discussionmentioning
confidence: 78%
“…Cirrus cloud formation is associated with upwelling motions, either due to frontogenesis or convection. It is also strongly driven by horizontal water vapor transport over a wide range of scales (local to continental), including isentropic advection (Fueglistaler et al, 2004;Keckhut et al, 2005;Montoux et al, 2010) and phase changes. Also, cyclones and airplane contrails provide conditions for cirrus cloud generation, presenting particular unique characteristics.…”
Section: E G Larroza Et Al: Towards An Automatic Lidar Cirrus Cloumentioning
confidence: 99%